LEADERSHIP MANAGEMENT OF PASUKAN AMAL SHOLEH (PASKAS) AT KAPAL MUNZALAN MOSQUE INDONESIA - Ngatin, jami; Cucu, Cucu (Jurnal Manajemen Dakwah, 2023)
Abstract This study was based on the fenomena of Kapal Munzalan Mosque Indonesia. The institution able to empower the youth potential ongoing the da'wah with mosque formation called PASKAS. They accomplished to broaden the volunteerism platform through few regions in Indonesia. On the other hand, PASKAS have a programme that continuously donated rice to the Pondok Pesantren, orphans and hafidz to serve their main staple. Nevertheless, this programme can be proceed with the leadership role of PASKAS. Heretofore, this study concerned on how the PASKASs' leadership management at Kapal Munzalan Mosque Indonesia. The research purposed to know 1) leadership planning of PASKAS, 2) leadership organization of PASKAS, 3) leadership development of PASKAS, 4) Leadership surveil and evalution of PASKAS. This study applied the qualitative approach with sample case by descriptive method. The data was collected with various process included interview, documentation and observation. Thereafter, the data analysis tehniques proceeding by data collection, data reduction, display and data verification. Move forward, the data validity check was implemented by extended the observation, triangulation and member check. As the result, this study shown 1) The leadership planning of PASKAS was performed by estimate phase, goals setting and development of policy procedure throughout the analysis process on the resources and surrounding. 2) The leadership organization of PASKAS hold by classification acctivities, deployment of human resources in the implementation of duty and delegation of authority for efficiency. 3) The leadership development of PASKAS using the principle of being educated and guided with a collaborative work pattern. The principle of being educated in mobilizing PASKAS has the goal of upgrading its human qualities, by establishing the status of PASKAS members not as volunteers but as students at the Kapal Munzalan Mosque Indonesia. Meanwhile, the guided principle aims to make the PASKAS movement systematic and organized, and carry out a congregational work pattern that aims to knit all the potential of the members so that they become a strength. 4) Monitoring of PASKAS leadership is carried out in stages and leadership evaluation of PASKAS is carried out continuously through monitoring results. Keywords: PASKAS, Leadership, Mosque